RELATIONSHIP BETWEEN CANCER AND THE KNOWLEDGE OF FOOD STORAGE IN THE FRIDGE OF PEOPLE IN SOME NORTHERN PROVINCES OF VIETNAM (Vietnam Journal of Community Medicine, 2022)
The cross-sectional study was carried out on 151 main housewives aged from 18 to 60 representing 151 households in Hanoi, Vinh Phuc and Yen Bai. In which, there are 75 households having cancer patients and 76 households not having cancer patients. The study aims to describe the knowledge of food preservation in the refrigerator, thereby to analyze some factors related to the knowledge of food preservation in the fridge between the two groups of households which mentioned before. In two research groups on subjects with cancer and without cancer, we found that the difference in knowledge between the two groups was quite clear and statistically significant (p-value
Keywords: Cancer, knowledge, food preservation, fridge/refrigerator.